2007
DOI: 10.1007/s10464-007-9102-7
|View full text |Cite
|
Sign up to set email alerts
|

Introducing systems change in the schools: the case of school luncheons and vending machines

Abstract: A major public health crisis facing America's society is the increase in child and youth obesity, which has seen a fourfold increase in the last four decades. Major concerns include what children eat for school lunch and what other foods are available in schools. This paper illustrates efforts towards systems change in the luncheon program and food vending machines in the Chicago Public Schools. We discuss the different factors that lead to such changes using the framework of the social ecological model and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 31 publications
2
30
0
2
Order By: Relevance
“…In fact, the evaluation report from the Coordinated School Health (CSH) program in Tennessee found that students' physical activity levels actually decreased during the first year of our study (CSH, 2008). Similar to other school-based research (Suarez-Balcazar et al, 2007), we found resistance to change due to a perpetuation of the status quo, a lack of school revenue and resources, and institutional bureaucracy. Evenson et al (2009) reported that, 'State legislation often mandates programs but does not offer sufficient guidance or resources to implement new policies ' (p. 236).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In fact, the evaluation report from the Coordinated School Health (CSH) program in Tennessee found that students' physical activity levels actually decreased during the first year of our study (CSH, 2008). Similar to other school-based research (Suarez-Balcazar et al, 2007), we found resistance to change due to a perpetuation of the status quo, a lack of school revenue and resources, and institutional bureaucracy. Evenson et al (2009) reported that, 'State legislation often mandates programs but does not offer sufficient guidance or resources to implement new policies ' (p. 236).…”
Section: Discussionsupporting
confidence: 84%
“…They proposed that SEM focuses attention on the contexts of behavior when designing, implementing or critically evaluating programs, and we argue that this can apply to physical education reform in schools. These data 'helped us understand the multiple perspectives of stakeholders which in this case were also a source of resistance to change and conflict' (Suarez-Balcazar et al, 2007;p. 345).…”
Section: Discussionmentioning
confidence: 99%
“…For example, one previous study found that nutrition classes were needed to enable elementary school students to select more fruit or vegetables when a salad bar was introduced. 21 In the Institute of Medicine Report, support for school food service staff was recommended. 3 This support could include marketing and presentation tips, as well as training for the food service staff to offer positive encouragement about the foods during meal service.…”
Section: Discussionmentioning
confidence: 99%
“…A special issue of the American Journal of Public Health in 2006 (86) and a special issue of the American Journal of Community Psychology in 2007 (45) featured articles on theory, methods, and models of complex systems thinking. These included case studies of system improvement by changing how a system is bounded (26), changing the mindset or "mental model" that people have about the environment or system that they are within (44), strengthening relationships (24), and providing new resources (123).…”
Section: The Complex Interventionmentioning
confidence: 99%